Access to Education Rights - A Case of Malawi - Kayuni, Samuel McNeil Elias (European Journal of Applied Sciences, 2025)
Access to education is a fundamental human right recognized by various international treaties and national constitutions. In Malawi, the right to education is enshrined in the Constitution and supported by policies aimed at promoting inclusive and equitable education for all citizens. However, significant barriers persist that hinder access to quality education, particularly for marginalized groups such as girls, children with disabilities, and those from impoverished backgrounds. This paper examined the current state of educational access in Malawi, highlighting key challenges such as inadequate infrastructure, insufficient funding, cultural attitudes towards education, and the impact of socio-economic factors. It also explored government initiatives and non-governmental efforts aimed at improving educational access and quality. The analysis underscores the importance of community involvement and policy reform in addressing these challenges. Furthermore, this study emphasizes the role of international organizations in supporting Malawi’s educational framework through funding and technical assistance. By identifying best practices and successful interventions, the paper aims to provide recommendations for enhancing access to education rights in Malawi, ensuring that every child has the opportunity to achieve their full potential through quality education. Ultimately, achieving universal access to education in Malawi requires a concerted effort from all stakeholders, including government agencies, civil society, and local communities, to create an inclusive educational environment that respect and promote the rights of every individual.